Nitrate Uptake Affects Cell Wall Synthesis and Modeling - Landi, Simone; Esposito, Sergio (Frontiers in Plant Science, 2017)
Nowadays, the relationship(s) about N assimilation and cell wall remodeling in plants remains generally unclear. Enzymes involved in cell wall synthesis/modification, and nitrogen transporters play a critical role in plant growth, differentiation and response to external stimuli. In this review a co-expression analysis of nitrate and ammonium transporters of Arabidopsis thaliana was performed in order to explore the functional connection of these proteins with cell-wall related enzymes. This approach highlighted a strict relationship between inorganic nitrogen transporters and cell wall formation, identifying a number of co-expressed remodeling enzymes. The enzymes involved in pectin and xyloglucan synthesis resulted particularly co-regulated together with nitrate carriers, suggesting a connection between nitrate assimilation and cell wall growth regulation. Major Facilitator Carriers, and one chloride channel, are similarly co-expressed with pectin lyase, pectinacetylesterase and cellulose synthase. Contrarily, ammonium transporters show little or no connection with those genes involved in cell wall synthesis. Different aspects related to plant development, embryogenesis and abiotic stress response will be discussed, given the importance in plant growth of cell wall synthesis and nitrate uptake. Intriguingly, the improvement of abiotic stress tolerance in crops concerns both these processes indicating the importance in sensing the environmental constraints and mediating a response. These evaluations could help to identify candidate genes for breeding purposes.